BIBLIOMETRIC TRENDS ON HALAL SCIENCE AND HALAL EDUCATION: A REVIEW - Yumi Zuhanis Has-Yun Hashim; Nurhusna Samsudin; Anis Najiha Ahmad; Nurhidayu Al-saari; Ibrahim Shogar; Maizatul Atiqah Yusof; Dinie Kaiyisah Mohamad Tauhid, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The global halal industry has grown significantly, driven by contributions from government, industry, academia, community, and environmental stakeholders. This growth underscores the importance of science and technology (S&T) and education in advancing the halal ecosystem. However, limited research has explored halal science within a holistic, faith-based framework or the development of formal halal curricula. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this study investigates publication trends and the body of knowledge in halal science and halal education. Using a bibliometric approach, data from Scopus were analysed through tools like VosViewer software v1.6.13 and Biblioshiny tools (RStudio 2023.12.0) while for Google scholar the search was done through Publish and Perish v8.0 . The study identified 155 Scopus and 96 Google Scholar entries, focusing on trends, thematic mappings, and keyword networks. Findings reveal increasing interest in both domains, with Scopus highlighting halal authentication, profiling, and halal meat research, while Google Scholar focuses on consumer behaviour and perceived knowledge. Both sources lack alignment with a holistic, tawhidic-based approach to halal science and have minimal attention to formal halal education curricula. Research in halal science remains tied to conventional S&T applications, and halal education primarily addresses consumer knowledge rather than structured learning. The study concludes that halal science needs a faith-based paradigm, and halal education requires formal integration into curricula to sustain the halal ecosystem. Future efforts should develop comprehensive halal curricula across educational levels and integrate tawhidic principles into halal science. These initiatives will bridge gaps, fostering innovation and sustainable growth in the halal industry.